Human Rights in the World community - Pierre Claude, Richard | Weston, Burns H. (University of Pennsylvania, Philadephia, 1992)
Specifically designed for educational use by international relations, law, and political and social science classes, Human Rights in the World Community treats the full range of human rights issues, including implementation problems and processes involving international, national, and nongovernmental action